2015
DOI: 10.1007/s10151-015-1351-0
|View full text |Cite|
|
Sign up to set email alerts
|

Implantation of autologous muscle-derived stem cells in treatment of fecal incontinence: results of an experimental pilot study

Abstract: BackgroundThe aim of this study is to present results of the implantation of autologous myoblasts into the external anal sphincter (EAS) in ten patients with fecal incontinence.MethodsAfter anatomical and functional assessment of the patients’ EAS, a vastus lateralis muscle open biopsy was performed. Stem cells were extracted from the biopsy specimens and cultured in vitro. Cell suspensions were then administered to the EAS. Patients were scheduled for follow-up visits in 6-week intervals. Total follow-up was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 32 publications
6
54
0
Order By: Relevance
“…One of the ten patients was lost to follow up during the study period. By 18 weeks of follow-up, twothirds of the patients (n = 6) reported subjective improvement in symptoms and over half had improved quantitative parameters of rectal function; however, after 1 year of follow-up, two of these patients exhibited a decline in both their qualitative and quantitative improvements [1]. This report by Romaniszyn et al [1] is among the first to independently confirm the clinical observations from Frudinger et al [5].…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…One of the ten patients was lost to follow up during the study period. By 18 weeks of follow-up, twothirds of the patients (n = 6) reported subjective improvement in symptoms and over half had improved quantitative parameters of rectal function; however, after 1 year of follow-up, two of these patients exhibited a decline in both their qualitative and quantitative improvements [1]. This report by Romaniszyn et al [1] is among the first to independently confirm the clinical observations from Frudinger et al [5].…”
mentioning
confidence: 53%
“…They designed their study based in part on (a) a preclinical rat model reporting that the injection of bone marrow-derived mesenchymal stem cells (MSC), also known as multipotent stromal cells [2], (b) quantitatively improved objective measures of fecal incontinence [3,4]; and (c) a pilot clinical study by Frudinger et al [5] reporting that women with fecal incontinence showed objective improvement in rectal function for up to 1 year following injection of skeletal muscle-derived cells. Here, Romaniszyn et al [1] report positive outcomes in a pilot study treating fecal incontinence with autologous skeletal muscle cell injection. The authors enrolled ten patients (nine females and one male) with severe fecal incontinence that had persisted despite 6 months of conventional biofeedback therapy.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…To simplify the cell isolation and proliferation process, Mazzanti et al used freshly isolated minimally manipulated bone‐marrow derived mononuclear cells without expansion and found them to be as effective as in vitro expanded BM‐MSCs in the recovery of iatrogenic anal sphincter rupture 38. Muscle‐derived stem cell injections have been used in small pilot studies in women and the results are promising 39, 40, 41. Frudinger et al treated 10 patients with autologous myogenic stem cells and found a significant improvement in the AI symptoms at 1‐ and 5‐year controls.…”
Section: Discussionmentioning
confidence: 99%
“…It is a pleasure to provide the commentary on the pioneering work of Dr. Romaniszyn and colleagues entitled: ''Implantation of autologous muscle-derived stem cells in treatment of fecal incontinence: Results of an experimental pilot study'' [1].…”
mentioning
confidence: 99%